ANALISIS VALIDITAS MEDIA VIDEO PEMBELAJARAN ANIMASI BERMUATAN TRI HITA KARANA MATERI BAGAIMANA KITA HIDUP DAN BERTUMBUH MATA PELAJARAN IPAS DI SEKOLAH DASAR - I Gede Agus Arya Sudarmika; Kadek Hengki Primayana; L. Heny Nirmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the condition where the lecture method still dominates as the main approach most commonly applied, as well as the limitations of audio-visual-based learning media that are contextually based on local content in elementary school IPAS learning. The material